Acetylcholine Inhibits Monomeric C-Reactive Protein Induced Inflammation, Endothelial Cell Adhesion, and Platelet Aggregation; A Potential Therapeutic? - Slevin, Mark; Iemma, Rocco S.; Zeinolabediny, Yasmin; Liu, Donghui; Ferris, Glenn R.; Caprio, Vittorio; Phillips, Nicola; Di Napoli, Mario; Guo, Baoqiang; Zeng, Xianwei; AlBaradie, Raid; Binsaleh, Naif K.; et al. (Frontiers in Immunology, 2018)
Objectives: In this study, we examined the possibility of using targeted antibodies and the potential of small molecular therapeutics (acetylcholine, nicotine and tacrine) to block the pro-inflammatory and adhesion-related properties of mCRP. Methods: We used three established models (platelet aggregation assay, endothelial leucocyte binding assay and monocyte inflammation via ELISA and Western blotting) to assess the potential of these therapeutics. Results: The results of this study showed that monocyte induced inflammation (raised TNF-α) induced by mCRP was significantly blocked in the presence of acetyl choline and nictotine, whilst tacrine and targeted antibodies had less or no significant effects. Western blotting confirmed the ability of acetylcholine to notably block mCRP-induced cell signalling phosphorylation of p-ERK1/2, and p-p38 and NF-κB. There was no evidence of direct binding between small molecules and mCRP. mCRP also induced endothelial cell-monocyte adhesion in a dose dependent fashion, however, both acetylcholine and nicotine as well as targeting antibodies (1:10 dilution) notably inhibited adhesion. Finally, we investigated their effects on mCRP-induced platelet aggregation. All three small molecules significantly attenuated platelet aggregation as did the antibody 8C10 although 3H12 had a weaker effect. Discussion: Acetylcholine and to a lesser extent nicotine show potential for therapeutic inhibition of mCRP-induced inflammation and cell and platelet adhesion. These results highlight the potential of targeted antibodies and small molecule therapeutics to inhibit the binding mCRP via blocking membrane binding and subsequent activation of cellular cascade systems, which produce the pro-inflammatory effects associated with mCRP.